Design of high-speed clock and data recovery circuits - Tan, Kok Siang; Sulaiman, Mohd Shahiman; Chuah, Hean Teik; Sachdev, Manoj (Springer US, 2007)
This article describes the various architectures for a high-speed clock and data recovery (CDR) circuit. Following a brief introduction of clock and data recovery circuit, a phase detection circuit, one of the most critical blocks in a CDR that determines not only the performance but also the CDR architecture, is addressed. The descriptions start with the most basic XOR logic up to the phase-frequency detector circuit. Trade-offs of each of the phase detectors are outlined. Two types of dual loop CDR architecture are briefly introduced. Finally, full-rate and half rate CDR architectures are described.